Stigma and functioning in patients with bipolar disorder (2011)
Objective: The aim of this study was to investigate the impact of self-rated stigma and functioning in patients with bipolar disorder in Latin-America. Methods: Two-hundred and forty-one participants with bipolar disorder were recruited from three Latin American countries (Argentina, Brazil, and Colombia). Functional impairment was assessed with the Functioning Assessment Short Test (FAST) and experiences with and impact of perceived stigma was evaluated using the Inventory of Stigmatizing Experiences (ISE). Results: Higher scores of self-perceived stigma were correlated with lower scores of functioning. After multiple regression analysis, being on disability benefit, current mood symptoms and functioning were associated with self-perceived stigma. Conclusions: This is the first study to demonstrate an association between stigma and poor functioning in bipolar disorder. Possible implications of such findings for practitioners are discussed. Limitations: The main limitation of this study is that the Inventory of Stigmatizing Experiences has not yet been validated in a population of bipolar patients in our countries. The sample size and heterogeneous clinical subjects from different countries and cultures limit the generalization of the present findings. © 2010 Elsevier B.V.